O novo Leviatã: a agenda anticorrupção e a expansão do neoliberalismo no Brasil - Forattini, Fernando Miramontes (2023)
This thesis explores the relationship between the discourse and the anti-corruption agenda in Brazil, during the period from 1945 to 1964, and the implementation of politicaleconomic measures of neoliberal rationality, as well as their implications in the politicalsocial arrangement of the country and in the political culture Brazilian. I propose a new way of understanding the topic of corruption, no longer as an instrument of social manipulation, but as an element endowed with rationality that goes beyond the idea of political instrumentalization, as it is part of the neoliberal essence. For this, I use the perspective proposed by new studies that identify the principles of neoliberalism already in the post 1st World War as a way to contain social aspirations and state intervention. It is a conservative ideology that just as it uses austerity to achieve its goals (Mattei 2022), it uses the anti-corruption agenda, its moralist and, allegedly, technical arm. Being conservative, it manages, in order to achieve its objectives, to harmonize with other forms of conservatism movements, as occurred in the civil-military coup of 1964. From this theoretical reconfiguration, we can understand the anti-corruption agenda as a means of combating any model of state planning, while seeking to diminish it by representing it as corrupt, as well as any class linked to it. On the other hand, this discourse will be used to protect and expand the “free market”, allegedly exempt from political disputes, driven by the efficiency of the “free hand”. The issue of anti-corruption also has another agenda, such as the need for legislation and regulation to contain fraud in the private sector and in the formation of trusts, aiming not only to overcome one of the biggest problems in Brazil, the lack of foreign exchange for investment, but also to gradually eliminate the power of the government in making decisions, in favor of private rationale via private credits and direct investments in the Stock Exchange, which will consolidate itself as a source of power and investment as pro-market regulations are implemented in the country. I show that these were toothless regulations, as no actor will be punished, but the discourse of a regulated market was obtained, counterpointing the negative perception of a corrupt State. This theorization and methodology that I propose here allows us to investigate not only the selectivity present in anti-corruption political discourses, but also to understand that there is rationality behind these discourses and agenda, allowing the investigation of cases of private corruption through the same perspective and in the same work, previously studied in separated, but which are now part of the same theoreticalmethodological framework: the implementation of neoliberalism in Brazil